ANALISIS RISIKO DAN KEAMANAN DALAM LAYANAN PERBANKAN ONLINE: STUDI LITERATUR - Mahardhika, Mustafidah; Urika (Universitas Nusantara PGRI Kediri, 2025)
The development of digital technology has driven a major transformation in the banking system, particularly through online banking services that provide easy access for customers. However, this progress has also been accompanied by an increase in cybercrime risks that threaten the security of financial institutions. This study aims to analyze the forms of risk and security threats in digital banking services, evaluate the mitigation strategies that have been implemented, and provide recommendations for strengthening the digital banking security system in Indonesia. The method used is a literature study by reviewing national journals and publications from the Financial Services Authority (OJK). The results of the study show that the main risks faced by banks include phishing attacks, malware, and personal data leaks that impact both financial institutions and customers. The mitigation strategies implemented have not been fully effective due to weak supervision and uneven implementation. Therefore, a comprehensive approach is needed through strengthening security technology, improving cyber governance, increasing digital literacy, and collaborating on research and innovation to build a sustainable digital banking ecosystem.